Antimicrobial Resistance Pattern of Bacterial Isolates in Urine of the Children Suffering from UTI - Mawa, Imranul; Mazumder, Pranay Kumar; Barua, Ripon; Roy, Banani (IAHS Medical Journal, 2022)
Background : Use of antibiotics are important in the treatment of Urinary Tract Infections (UTIs). However, the inappropriate use of antibiotics contributing to the development of antimicrobial resistance. Urine culture is the most common and important laboratory test to isolate the microbial agents, their susceptibility pattern and subsequently helps in the selection of appropriate antimicrobial to treat the infection. To isolate and identify the bacterial agents in urine of children suffering from suspected urinary tract infection and determine their antimicrobial resistance pattern this research was performed. Materials and methods: This retrospective study was conducted in the Department of Microbiology, IAHS, Chattogram, Bangladesh from March 2019 and April 2020. Total 2100 urine specimens were collected from the children attended in IAHS Inpatients and Outpatients Department of pediatrics at BBMH with suspected urinary symptoms. Bacterial culture and antimicrobial susceptibility testing were done in all urine specimens in BBMH Microbiology laboratory. The isolated samples were classified according to their age, sex, microorganisms and antibiotic susceptibility. Patients were divided into different age groups which are 0-2, 2-6, 6-12 and 12-17 years. Results: Out of total 2100 urine samples, 720 samples showed bacterial growth on culture. That revealed the prevalence of UTI among child about 34%. The most common isolated bacterial agents was Escherichia coli (68.01%), Klebsiellapneumoniae (19.86%), Klebsiellaoxytoca (3.34%), Enterobacter cloacae (2.23%), and Pseudomonas aeruginosa (1.95%). In the 0-2 years age group was significantly high in this group (p<0.05) in terms of infectious agents diversity and antibiotic resistance. Isolated bacterial agents shows resistance to ampicillin (70.2%), amoxicillin- clavulanate (49.0%), cefixime (38.2%), and trimethoprim/sulfamethoxazole (37.1%). The frequency of UTIs were found more in girls (56.6%) than that of boys among 0-2 year age group. Conclusion: In conclusion, ampicillin, cephalosporins, amoxicillin-clavulanate, and TMP/SMX should not be empirically commenced. In order to avert a rapid resistance development that is closely associated with widespread and inappropriate antibiotic use, the use of random antibiotics should be avoided and particularly the 3rd generation cephalosporins should be used more selectively. Although our data reflect only the results of patients admitted to a single hospital, classification of pathogens and determination of resistance rates against oral and parenteral antibiotics make this study valuable as it assesses the resistance patterns in the patients. IAHS Medical Journal Vol 4(2), December 2021; 17-23